Combating The Macau Scam In Malaysia: Strategies For Mitigation And Resolution From Civil Law And Sharī'ah Perspectives - Nurul Anessa Rosley; Norman ZakiyyChow Jen-T’Chiang; Hasnizam Hashim (Intelligentia Resources, 2024)
Non-Indexed Publication